The Influence of Facial Asymmetry on Genuineness Judgment - Delor, Bérénice; D’Hondt, Fabien; Philippot, Pierre (Frontiers in Psychology, 2021)
This study investigates how asymmetry, expressed emotion, and sex of the expresser impact the perception of emotional facial expressions (EFEs) in terms of perceived genuineness. Thirty-five undergraduate women completed a task using chimeric stimuli with artificial human faces. They were required to judge whether the expressed emotion was genuinely felt. The results revealed that (a) symmetrical faces are judged as more genuine than asymmetrical faces, and (b) EFEs’ decoding is modulated by complex interplays between emotion and sex of the expresser.